Sensitivity and specificity of speckle tracking echocardiography for coronary artery disease: a systematic review and meta-analysis - Linping Xu; Haoqi Xu; Zhi Pan; Ruizhong Ye (Frontiers in Cardiovascular Medicine, 2026)
Objectives To determine the diagnostic performance of various myocardial strain parameters obtained by speckle-tracking echocardiography for detecting coronary artery disease. Methods PubMed, Embase, Web of Science, and Cochrane Library were systematically searched from inception to 1 September 2025. Eligible studies included patients with suspected CAD, used CAG as the reference standard, and reported STE-derived strain parameters (e.g., GLS, GCS, GRS, GAS). Methodological quality was assessed via QUADAS-2, and meta-analyses were performed using a bivariate hierarchical random-effects model in STATA 18.0. Results A total of 40 non-randomized studies involving 5,296 participants were included. The overall pooled sensitivity and specificity of STE for CAD were 77.3% (95% CI: 73.4–80.8%) and 75.0% (95% CI: 71.5–78.1%), respectively, with substantial heterogeneity across studies. Subgroup analyses suggested that global longitudinal strain (GLS) had more optimal performance (sensitivity: 78.6%, 95% CI: 74.5–82.2%; specificity: 76.3%, 95% CI: 72.7–79.7%), while global area strain (GAS) showed the highest sensitivity (83.3%, 95% CI: 74.5–89.5%) but moderate specificity (72.2%, 95% CI: 58.9–82.5%). Exercise stress STE demonstrated higher sensitivity than dobutamine stress or no stress protocols, and recovery-phase measurements showed promising but imprecise results. Deek's funnel plot indicated no significant publication bias ( P = 0.202). GRADE assessment rated the overall certainty of evidence as low due to high risk of bias, indirectness, and imprecision. Conclusion STE exhibits moderate diagnostic accuracy for CAD, with GLS being the most robust parameter. Future research should focus on standardizing methodologies, validating strain thresholds, and integrating STE into multidisciplinary diagnostic pathways. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/view/CRD420251207466 .